A balance between glycitein and glyceollins governed by isoflavone 6-hydroxylase confers soybean resistance to Phytophthora sojae - Qilin Yang; Yining Wang; Xindan Xu; Jia Yuan; Fengxia Zhang; Hao Qin; Shihao Li; Jianxu Li; Hao Lin; Lei Li; Zhixi Tian; Guodong Wang (Proceedings of the National Academy of Sciences, 2025)
Isoflavonoids, predominantly found in legumes, are specialized metabolites with antioxidant properties that benefit both plant resilience and human health. Using metabolic genome-wide association studies (mGWAS), we identified the cytochrome P450 gene ( Glyma.11g108300 ), GmIF6H1 , as a key determinant of glycitein biosynthesis in soybean [ Glycine max (L.) Merr.]. Biochemical assays together with in planta stable-isotope tracing demonstrated that GmIF6H1 catalyzes the 6-hydroxylation of daidzein, establishing a previously unrecognized and predominant biosynthetic route for glycitein. A single amino acid substitution in GmIF6H1 accounts for the domestication-associated reduction of glycitein-type isoflavonoids. Upon Phytophthora sojae infection, (malonyl)glycitins undergo sustained deglycosylation to release glycitein aglycone, underscoring its defensive role. Strikingly, both loss- and gain-of-function alleles increase susceptibility to P. sojae , indicating that precise tuning of GmIF6H1 expression is essential for effective resistance. Metabolite profiling further reveals complementary daidzein-centered defense strategies: Glycitein-type isoflavonoids (via daidzein 6-hydroxylation) function as phytoanticipins, whereas glyceollins (via daidzein 2’-hydroxylation) act as inducible phytoalexins. Together, these findings clarify the biosynthetic origin of the glycitein and underscore the synergistic action of glycitein and glyceollins in pathogen resistance, offering opportunities for engineering disease-resilient soybean cultivars.